Psychometric properties of a Spanish-version of the Schizophrenia Objective Functioning Instrument (Sp-SOFI) (2023)
The Schizophrenia Objective Functioning Instrument (SOFI) is an interviewer-administered scale designed to objectively assess the actual level of patient functioning and to measure community functioning related to cognitive impairment and psychopathology. The aim was to examine the psychometric properties of the Spanish version of the SOFI (Sp-SOFI) in a sample of 155 Spanish outpatients with schizophrenia disorder. The instruments applied were Sp-SOFI, Positive and Negative Syndrome Scale (PANSS), Clinical Global Impression-Schizophrenia Scale (CGI-SCH), Personal and Social Performance Scale (PSP), and Global Assessment of Functioning (GAF). The discrimination indexes of the Sp-SOFI items range from .21 to .77. Exploratory factor analysis showed an essentially one-dimensional structure. Cronbach's alpha was .93. Test-retest reliability for the Sp-SOFI total score was .87 (p < .001). The canonical correlation between SP-SOFI domains and PSP dimensions was .83. The multiple correlation coefficient between Sp-SOFI domains and GAF score was .84. Sp-SOFI scores were significantly different between high and low scores on the PANSS scales (p < .001). Sp-SOFI measures discriminated among patients with doubtful, mild, moderate, and severe schizophrenia disorder according to CGI-SCH scales (p < .001). New evidence about the validity of the SOFI was provided. The Sp-SOFI is a reliable and valid tool for using in clinical practice. © 2015 Asociación Española de Psicología Conductual.